The SNPs of mitochondrial DNA displacement loop region and mitochondrial DNA copy number associated with risk of polymyositis and dermatomyositis - Zhao, Yufei; Peng, Chenxing; Lai, Ruixue; Zhang, Jingjing; Zhang, Xiaoyun; Guo, Zhanjun (Scientific reports, 2022)
Oxidative damage-induced mitochondrial dysfunction may activate muscle catabolism and autophagy pathways to initiate muscle weakening in idiopathic inflammatory myopathies (IIMs). In this study, Single nucleotide polymorphisms (SNPs) in the mitochondrial displacement loop (D-loop) and mitochondrial DNA (mtDNA) copy number were assessed and their association with the risk of polymyositis and dermatomyositis (PM/DM) was evaluated. Excessive D-loop SNPs (8.779 ± 1.912 vs. 7.972 ± 1.903, p = 0.004) correlated positively with mtDNA copy number (0.602 ± 0.457 vs. 0.300 ± 0.118, p < 0.001). Compared with that of the controls, the mtDNA of PM/DM patients showed D-loop SNP accumulation. In addition, the distribution frequencies of 16304C ( p = 0.047) and 16519C ( p = 0.043) were significantly higher in the patients with PM/DM. Subsequent analysis showed that reactive oxygen species (ROS) generation was increased in PM/DM patients compared with that in the controls (18,477.756 ± 13,574.916 vs. 14,484.191 ± 5703.097, p = 0.012). Further analysis showed that the PM/DM risk-related allele 16304C was significantly associated with lower IL-4 levels ( p = 0.021), while 16519C had a trend to be associated with higher IL-2 expression ( p = 0.064). The allele 16519C was associated with a positive antinuclear antibody (ANA) status in PM/DM patients ( p = 0.011). Our findings suggest that mitochondrial D-loop SNPs could be potential biomarkers for PM/DM risk and these SNPs associated with cytokine expression may be involved in the development of PM/DM. Further, mtDNA copy number-mediated mitochondrial dysfunction may precede the onset of PM/DM.